The Application of PCK Concept and Information Fusion-Oriented Multimedia Technology in Music Education. (7th October 2022) - Yin, Yunzhi
Abstract : In order to improve the teaching effect of modern music, this paper combines the concept of PCK with information fusion-oriented multimedia technology to explore methods that can improve the quality of music education, and recharacterizes propositional subject knowledge in a way that students like to hear. Moreover, combined with the teaching practice of music teachers in colleges and universities, this paper sorts out the theoretical framework of this research, in order to establish a paradigm suitable for college music teachers to improve music PCK. In addition, this paper constructs an intelligent music teaching system based on multimedia technology and PCK concept. From the experimental research results, it can be seen that the PCK concept and information fusion-oriented multimedia technology have obvious application effects in music education, and can effectively improve the educational effect of modern music.